2014
DOI: 10.1017/s0007114514000129
|View full text |Cite
|
Sign up to set email alerts
|

Compared with that of MUFA, a high dietary intake ofn-3 PUFA does not reduce the degree of pathology in mdx mice

Abstract: Duchenne muscular dystrophy (DMD) is a severe muscle disease that affects afflicted males from a young age, and the mdx mouse is an animal model of this disease. Although new drugs are in development, it is also essential to assess potential dietary therapies that could assist in the management of DMD. In the present study, we compared two diets, high-MUFA diet v. high-PUFA diet, in mdx mice. To generate the high-PUFA diet, a portion of dietary MUFA (oleic acid) was replaced with the dietary essential n-3 PUFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…These findings reinforce the idea that endogenously produced fatty-acids are likely functionally distinct from fatty acids imported from circulation or intracellular triglyceride lipolysis [4547]. We incubated myotubes in OA, EPA, or DHA in addition to PA because of data suggesting that saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids may differentially affect muscle functions in muscular dystrophy [48, 49]. Neither OA, EPA, nor DHA had an effect on SERCA-dependent Ca 2+ uptake.…”
Section: Discussionsupporting
confidence: 63%
“…These findings reinforce the idea that endogenously produced fatty-acids are likely functionally distinct from fatty acids imported from circulation or intracellular triglyceride lipolysis [4547]. We incubated myotubes in OA, EPA, or DHA in addition to PA because of data suggesting that saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids may differentially affect muscle functions in muscular dystrophy [48, 49]. Neither OA, EPA, nor DHA had an effect on SERCA-dependent Ca 2+ uptake.…”
Section: Discussionsupporting
confidence: 63%
“…Plasma glycerol (a marker of whole body lipolysis) and plasma TG concentrations were measured using a commercially available kit (Sigma-Aldrich). For measurement of hepatic TG concentration, lipids were extracted from ϳ8 mg of tissue, and TG content of the extract was determined using a commercially available kit (Sigma-Aldrich) (18,23) and expressed as percentage of liver wet weight.…”
Section: Methodsmentioning
confidence: 99%
“…Dawn Brasaemle of Rutgers University), MTP (1:100,000; BD Transduction Laboratories, San Jose, CA), cAMP response element-binding protein (CREB) (1:500; Cell Signaling Technology), phospho-CREB Ser133 (1:1,000; Cell Signaling Technology), and ␤-actin (1:2,000; Cell Signaling Technology). Membranes were then incubated with IR Dye 680 (1:10,000; LI-COR Biosciences, Lincoln, NE) or IR Dye 800 (1:10,000; LI-COR Biosciences) secondary antibodies and bands quantified with ␤-actin as a loading control (23).…”
Section: Methodsmentioning
confidence: 99%
“…Further, initial observations suggest that ω 3 PUFA supplementation with fish oil or EPA decreases muscle degeneration and inflammation in mdx mouse model mirrored by reduced functional impairment evaluated by grip strength tests [207, 208]. On the contrary, by using a highly controlled diet design, Henderson et al [209] have recently put forward a detrimental effect of a high intake of ω 3 PUFA, unlike high MUFA, in the same animal model as demonstrated by higher serum CK activity and no changes in skeletal muscle histopathology and inflammatory markers (p65) [209]. Congruent with the latter observations, Galvao and coworkers [210] have recently demonstrated that high ω 3-PUPA diet enriched with α-linoleic and α-linolenic acid, unlike high long chain saturated fatty acids diet, promotes a negative effect on lifespan in the same animal model with genetic cardiomyopathy.…”
Section: ω3 Long Chain Polyunsaturated Fatty Acids (ω3 Lc-pufas)mentioning
confidence: 99%